A critical analysis of the failure of nurses to raise concerns about poor patient care. (28th October 2016) - Roberts, Marc
Abstract: The occurrence of poor patient care is emerging as one of the most significant, challenging, and critical issues confronting contemporary nursing and those responsible for the provision of health care more generally. Indeed, as a consequence of the increased recognition of the manner in which nurses can be implicated in the occurrence of poor patient care, there has been sustained critical debate that seeks to understand how such healthcare failings can occur and, in particular, why nurses seemingly fail to intervene, raise concerns, and effectively respond to prevent the occurrence and continuation of such poor patient care. In seeking to contribute to this critical discussion, and in contrast to those "situational explanations" that maintain that the failure to raise concerns is a consequence of the contextual factors and challenging conditions to which nurses can be subject in the clinical setting, this paper will provide a resolutely philosophical analysis of that failure. In particular, it will draw upon the work of Jean‐Paul Sartre—the French philosopher generally regarded as one of the most influential thinkers of the twentieth century—in order to propose that his work can be productively recontextualized to provide a detailed, challenging, and provocative critical analysis of the occurrence and continuation of poor patient care and the role of individual nurse practitioners in such healthcare failings.